Výskum spokojnosti českých bankových klientov a porovnanie so situáciou na Slovensku - Belás, Jaroslav (Vysoké učení technické v Brně, Fakulta podnikatelská, 2013)
The satisfaction of banking clients determines their loyalty and willingness to buy product of the commercial bank. Many of researches and knowledge of banking practices show that there is a big group of dissatisfied customers. The aim of this article was compare the overall level of satisfaction of Czech and Slovak banks’ customers and quantify the most significant factors of satisfaction and dissatisfaction of these customers. Next aim was to define current trends of customers’ satisfaction in relation with the financial performance and the competitiveness of commercial banks. The research about satisfaction of retail customers in Czech and Slovak Republic has been realized through the questionnaire survey. Our research has confirmed that between Czech and Slovak republic exist very similar trends in the area of an overall satisfaction and partial reasons of satisfaction, respectively dissatisfaction of banks’ clients. The most significant reason of customers’ satisfaction is the possibility to use e-banking in both countries. For Czech banking clients is this reason more important than for the Slovak one. The most significant reason of dissatisfaction of banks’ clients is the price policy of banking products and services. The level of dissatisfied clients with this reason is approximately the same in both countries. Customers in both countries feel a low level of acceptance of their financial needs during the sales process. An interesting trend has been observed that satisfied clients use fewer amounts of banks and the value of cross-selling is lower than in the case of dissatisfied clients. A current situation on the Czech and Slovak banking market means, that banks have enough sales opportunities, if they are able to increase a customers’ satisfaction. Purpose of the article: The aim of this article was to quantify and compare the overall satisfaction between Czech and Slovak banks‘customers. Purpose of this article was to define the most important factors of satisfaction and dissatisfaction of banks‘customers and current trends in the area of customers‘satisfaction. Methodology/methods: The research of customers‘satisfaction in Czech and Slovak Republic has been conducted through the questionnaire survey. Set scientific hypothesis has been verified by Pearson chi/square test statistics to determine dependencies in the Pivot table. Methods of descriptive statistics and the weighted average have been used. Scientific aim: Scientific aim was to quantify and compare the overall satisfaction and the most significant reasons of satisfaction and dissatisfaction of Czech and Slovak banks‘clients. Next aim was to examine the impact of clients‘satisfaction on the usage of banking products and banks and to determine the change of the approach of commercial during the crisis. Findings: The overall customers‘satisfaction in Czech Republic and Slovakia is approximately on the same level. The most important reasons of customers‘satisfaction are the possibility to use e-banking in both countries. This trend is more important for Czech banking customers than for Slovak one. The most important dissatisfaction of customers is the price policy of banking products and services. The level of dissatisfied clients with this factor is the same in both countries. Czech and Slovak clients intensively feel the fact that bank just want to sell them their product and earn money and they are not interested in real solution of their financial issue anymore. However, customers of commercial banks still think that banks‘approach has been improved during the crisis. Our research has found out that commercial banks offer their products with low intensity in both countries. Satisfaction of customers significantly determines the amount of used banks. Conclusions: A satisfaction of banks‘customers represents a key parameter of financial performance and competitive ability of a commercial bank. Despite this fact, there exist a big group of dissatisfied clients and many activities of the banks which are not sufficient at all. Our research has been conducted on the sample of representative respondents and has brought some interesting notices which are going to be as the topics of our next researches and are going to be examined more specifically. In the same time, some opportunities to increase the satisfaction of customers which are able to be done in a short period and at minimal cost, has been presented. The very important possibility to increase a customers‘satisfaction is the growth of employees‘satisfaction in the bank.
The Research of Satisfaction of Czech Banking Clients and the Comparison of this Issue with Slovakia
Keywords: banks; customers‘satisfaction; reasons of satisfaction; reasons of customers‘dissatisfaction, the acceptance of clients‘needs